Analisis Tingkat Kepuasan Pasien Atas Pelayanan Zaal Kebidanan Dan Kandungan Pada RSUD Hamba Muara Bulian - Ratna Ratna; Nadiatul Khoiroh (CITRA EKONOMI, 2020)
One of the targets of Obstetrics and Gynecology at the general hospital of bulian estuary, namelyincreasing the level of patient satisfaction so that this becomes one of the indicators for measuringservice quality. One of the main elements supporting the level of patient satisfaction is patients withtheir resources. The purpose of the study was to determine the level of patient satisfaction with thequality of care in obstetrics and gynecology at the general hospital of bulian estuary. Respondents werepatients with obstetrics and gynecology at 75 general hospitals in the bulian estuary servants. Methodsof collecting data using questionnaires, observation, documentation. To test the hypothesis, thetechnique used is path analysis. Research results: (1) the quality of services in obstetrics andgynecology is very good, (2) the level of patient satisfaction with obstetrics and gynecology is very good. Advice for obstetrics and gynecology public hospitals in bulian estuary servans must improve servicequality and maintain then maintain existing quality must be done, so that customers or users of thehospital do not feel disappointed and the service users do not move elsewhere.